TO THE QUESTION OF THE ORIGIN OF THE VOCABULARY OF THE MODERN RUSSIAN LANGUAGE - Khojaeva Feruza Muzaffarovna (American Journals, 2023)
The vocabulary of the modern Russian language has been formed over the centuries. Vocabulary is based on original Russian words. A word that originated in the Russian language according to the models existing in it or passed into it from an older predecessor language - Old Russian, Proto-Slavic or Indo-European is considered to be primordial.
Keywords: Vocabulary, modern Russian language, words, Old Russian, Proto-Slavic, Indo-European.